Mobile telephone-delivered Contingency Management (mCM) to reduce heroin use in individuals with opioid use disorder (CM4OUD): A feasibility study protocol - Carol-Ann Getty; John Strang; Ewan Carr; Jesse Dallery; Nicola Metrebian (PLoS ONE, 2025)
Background Opioid use disorder (OUD) is a major public health issue and recovery is a long-term and complex process. Opioid Agonist Treatment (OAT) including medications such as methadone and buprenorphine, is the first-line medical intervention for OUD, however clinical responses among sub-populations differ and concurrent heroin use among individuals in OAT is reported. Contingency management (CM) is a behavioural intervention involving the application of positive reinforcement (e.g., monetary incentives) contingent upon evidence of positive behaviour change. CM is based on the theoretical principles of operant conditioning and is among the most efficacious psychosocial intervention in promoting substance use-related behaviours, including abstinence from smoking, alcohol and illicit drugs, medication adherence, vaccination uptake and attendance. Technology can be leveraged to expand the reach and accessibility of these interventions, automating key components of intervention delivery, including objective behaviour monitoring and immediate reward delivery. Currently, there are no fully remote CM interventions specifically targeting heroin use among individuals undergoing treatment for OUD, highlighting a critical need for innovation in addressing this complex aspect of substance use. Developing and delivering a fully digitalised app-based CM intervention for reducing heroin use among individuals in treatment for OUD holds considerable potential. This paper provides a protocol for a feasibility study that aims to determine the acceptability and feasibility of conducting a future randomised controlled trial of the clinical effectiveness of app-based CM to encourage heroin abstinence among clients receiving OAT in UK drug treatment services. Methods Forty OAT service users in UK drug treatment services who continue to use heroin will be randomly assigned to either (1) OAT plus a smartphone app providing abstinence incentives or (2) standard OAT alone. Participants in the intervention arm will receive financial incentives contingent on heroin-negative toxicology results. Over a 12-week period, participants will receive thrice-weekly push notifications via the smartphone app when an oral saliva test is due. Participants will receive feedback upon submission and verified heroin-negative tests will result in notification of earnings. The primary outcome of this feasibility trial is the number of eligible service users recruited over the 6-month recruitment period. Other feasibility outcomes include intervention adherence, drug screening completion and follow-up rates. Acceptability will be explored among both clinicians and service users. Progression to a larger confirmatory trial will be evaluated based on the pre-specified progression criteria. Discussion Research on CM has grown exponentially over the last decade, with remote technologies being leveraged more than ever to expand the reach and scope of these interventions. This study will evaluate the feasibility of a mCM app to support heroin abstinence among OAT recipients. By integrating CM with mobile technology, this approach could enhance treatment accessibility and effectiveness, potentially improving outcomes for a high-risk population.